CHEMICAL QUALITY OF DANGKE CHEESE FROM COW’S MILK WITH LIME COAGULANT: KUALITAS KIMIA KEJU DANGKE DARI SUSU SAPI DENGAN KOAGULAN EKSTRAK JERUK NIPIS - Windyasmara, Ludfia; Wicaksono, Arjun (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Cow's milk has good nutritional content for consumption and can be processed into processed products, one of which is dangke cheese. This study aims to determine the effect of the addition of lime in cow's milk dangke products on chemical quality and physical quality. This study had 5 treatments (addition of lime 0 ml, 0.5 ml, 1 ml, 1.5 ml, 2 ml). The research data will be analyzed using a Completely Randomized Design One Way Anova, and if the data has a significant effect P < 0.05, it will be continued with the Duncan Multiple Range Test. Based on the results of the study, the content of dangke cheese was 54.75–60.93%, pH 6.3–6.6, Yield 12.1–14.9% and texture 66.0-233.3g. The conclusion from the results of the study is that the addition of lime in the making of dangke has a very obvious different influence on moisture content, pH, yield and texture. Keywords: Lime, Dangke Cheese, Cow’s Milk.